Thinking for yourself developing critical thinking skills through reading and writing - Mayfield, Marlys (Wadsworth/Cengage Learning, 2014)
Rather than teaching from the "outside in" of rules and imitation, this title offers students an "inside out" approach for improving their own thinking, perceiving, writing, and awareness skills. Its hallmark features include cartoons, multiple options for application and testing, and explanation of critical thinking concepts and standards.